COMBINING ABILITY ANALYSIS IN THE INTERSPECIFIC CROSSES YSIS IN THE INTERSPECIFIC CROSSES OF CHILLI OF CHILL - K. ANANDHI; K. M. ABDUL KHADER (The Bioscan, 2019)
The combining ability of fifteen interspecific hybrids (Capsicum annuum x Capsicum frutescens) produced by crossing the parents in line x tester fashion along with their eight parentals, were tested for disease resistance and yield parameters. Combining ability analysis showed that the line Nenmara Local (60.80) and Thavanur Local (58.28) were alone good general combiners for fruit yield. Four hybrids viz., Mavelikkara Local x Jwalasakhi (165.79), Nenmara Local x Vellayani Athulya (135.61), Kayamkulam Local x Jwalamukhi (53.07) and Thavanur Local x Jwalamukhi (50.56) exhibited significant specific combining ability for fruit yield and except kayamkulam local x jwalamukhi all other three hybrids viz., Mavelikkara Local x Jwalasakhi (31.85), Nenmara Local x Vellayani Athulya (30.25) and Thavanur Local x Jwalamukhi (17.83)exhibited significant specific combining ability for number of fruits per plant. Nenmara local and jwalasakhi showed both significant general and specific combining ability for fruit yield. There is predominance of non-additive gene action for yield and yield components indicating that multiple parents having good GCA effects might prove to be useful.